1968
DOI: 10.1021/bi00852a028
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline phosphatase of Escherichia coli. Composition

Abstract: A rapid, single-step purification of the alkaline phosphatase of Escherichia coli using salt gradient chromatograpy on DEAE-cellulose is described. The product is homogeneous by electrophoretic and ultracentrifugal criteria and its amino acid composition is documented. The specific activity of the resultant enzyme is equivalent to that of the crystalline material (Malamy, M. H., and Horecker, B. L. (1964), Biochemistry 3, 1889).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
1

Year Published

1975
1975
2008
2008

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 34 publications
1
49
1
Order By: Relevance
“…MATERIALS AND METHODS Alkaline phosphatase was released by osmotic shock from the periplasmic space of E. coli cells treated with EDTA (2) Abbreviation: EPR, electron paramagnetic resonance. * To whom correspondence should be addressed.…”
Section: T)mentioning
confidence: 99%
See 1 more Smart Citation
“…MATERIALS AND METHODS Alkaline phosphatase was released by osmotic shock from the periplasmic space of E. coli cells treated with EDTA (2) Abbreviation: EPR, electron paramagnetic resonance. * To whom correspondence should be addressed.…”
Section: T)mentioning
confidence: 99%
“…The importance of zinc in both catalysis and structure stabilization of Escherichia coli alkaline phosphatase has long been recognized (1), but the presence of stoichiometric amounts of magnesium (1,2) has been largely ignored; hence, its role has remained both unappreciated and undefined. This study confirms the presence of stoichiometric quantities of magnesium in alkaline phosphatase and further demonstrates that this metal serves to regulate the mode of binding of zinc and increases enzymatic activities over and above those attained in the presence of zinc alone.…”
mentioning
confidence: 99%
“…This is reflected in the several bond as a short loop (nine intervening residues). The other was amino acid compositions that have been reported (6,29,30). formed by two peptides that were severed by performic oxiThese data, particularly those of Simpson et al (29), are in exdation and separated by gel filtration.…”
mentioning
confidence: 97%
“…The other was amino acid compositions that have been reported (6,29,30). formed by two peptides that were severed by performic oxiThese data, particularly those of Simpson et al (29), are in exdation and separated by gel filtration. Their location in CN II cellent agreement with the composition obtained from the seand CN lb was determined from their amino acid composition.…”
mentioning
confidence: 97%
“…Studies on Escherichia coli alkaline phosphatase (ECAP) have shown the importance of the divalent metal ions: Mg 2+ does not directly participate in the mechanism but is important for stabilization of the enzyme, whereas the two Zn 2+ ions are directly involved in catalysis (21,22). The Mg 2+ can affect the structure and function of molecular chromophores (23) as well as of many enzymes (24,25).…”
Section: +mentioning
confidence: 99%